Factors associated with treatment satisfaction in patients with rheumatoid arthritis: data from the biological register RABBIT. Issue 3 (13th October 2020) - Schäfer, Martin; Albrecht, Katinka; Kekow, Jörn; Rockwitz, Karin; Liebhaber, Anke; Zink, Angela; Strangfeld, Anja
Abstract : Objective: To assess satisfaction with the effectiveness and tolerability of treatments in patients with rheumatoid arthritis (RA). Methods: Patients from the RABBIT register, starting a biological (b) or targeted synthetic (ts) disease-modifying antirheumatic drug (DMARD), or a conventional synthetic (cs)DMARD treatment after ≥1 csDMARD failure, were included. Treatment satisfaction was measured after 1 year of treatment in four categories and binarised for analysis. Logistic regression models were performed to calculate ORs for factors associated with treatment satisfaction. Results: Data of 10 646 patients (74% women, mean 58 years) were analysed. At baseline, 55% of the patients were satisfied with the efficacy and 68% with the tolerability of their previously given treatments. After 1 year, 85% of the patients were satisfied with treatment effectiveness and 90% with tolerability. Baseline satisfaction (OR 2.98, 95% CI 2.58 to 3.44), seropositivity (OR 1.36, 95% CI 1.17 to 1.57), reduction of DAS28 (OR 1.38, 95% CI 1.31 to 1.46) and pain (OR 1.26, 95% CI 1.22 to 1.31), and the improvement of physical capacity (OR 1.22, 95% CI 1.17 to 1.29) were positively associated with treatment satisfaction at follow-up while glucocorticoids (GCs) >5 mg/day, depression, fibromyalgia, obesity, prior bDMARDs and therapy changes were negatively associated. The impact of GC on satisfaction was dose-dependent, becoming strongest for GC >15 mg (OR 0.24, 95% CI 0.16 to 0.34). A 5 mg/day reduction within 12 months was positively associated with satisfaction regarding efficacy (OR 1.19, 95% CI 1.11 to 1.27) and tolerability (OR 1.11, 95% CI 1.03 to 1.21). Conclusion: Most patients were satisfied with their treatment's effectiveness and tolerability after 1 year of treatment. Tapering GCs was positively associated with the improvement of patients' satisfaction.